Natural History of Non-Functioning Pituitary Adenomas: A Systematic Review and Meta-Analysis - Rikvold, Stefan Dukanovic; Pedersen, Mathias Brown; Andreassen, Mikkel; Krogh, Jesper (Hormone and Metabolic Research, 2023)
The management of non-functioning pituitary tumors (NFPTs) relies on the risk of tumor growth and new endocrinopathies. The objective of this systematic review was to assess the risk of growth, new pituitary endocrinopathies, and surgery in patients with conservatively treated NFPTs. We conducted a bibliographical search identifying studies assessing NFPTs followed conservatively. Estimates were pooled using random-effects meta-analysis reporting events per 100 person years (PYs), in case of high heterogeneity (I2>75%) only the range of observed effects was reported. We identified 30 cohort studies including 1957 patients with a mean follow-up time of 4.0 (SD 1.5) years. The overall risk of tumor growth ranged from 0.0 to 14.2/100 PYs (I2=90%), while the overall risk of new endocrinopathies was 0.9/100 PYs (95% CI. 0.5 to 1.2; I2=35%) and risk of surgery ranged from 0.0 to 7.7/100 PYs (I2=80%). Compared to microadenomas, macroadenomas had higher risk of growth (p=0.002), higher risk of surgery (p=0.006), and non-significant differences in risk of new endocrinopathies (p=0.15). An analysis of microadenomas found the risk of growth to be 1.8/100 PYs (95% CI. 0.9 to 2.8; I2=58%), the risk of new endocrinopathies 0.7/100 PYs (95% CI. 0.0 to 1.6; I2=37%) and the risk of surgery 0.5/100 PYs (0.1 to 0.9; I2=37%). These data support individualized follow-up strategies of patients with NFPTs and particularly a less rigorous follow-up of patients with microadenomas.
Keywords: non-functioning pituitary tumors; PitNets; natural history; endocrinopathies